How Boron Doping Shapes the Optoelectronic Properties of Canonical and Phenylene‐Containing Oligoacenes: A Combined Experimental and Theoretical Investigation. Issue 21 (27th March 2017) - Kirschner, Sven; Mewes, Jan‐Michael; Bolte, Michael; Lerner, Hans‐Wolfram; Dreuw, Andreas; Wagner, Matthias
Abstract: Optimized syntheses of 6, 13‐dimesityl‐6, 13‐dihydro‐6, 13‐diborapentacene (DBP ) and a related compound (DBI ) featuring two biphenylene‐2, 3‐diyl units in place of naphthalene‐2, 3‐diyl moieties are reported. Striking differences between the optoelectronic properties ofDBP andDBI have been experimentally observed, and explained by quantum chemical calculations.DBP is a member of the oligoacene family, DBI is a linear [ N ]phenylene derivative. The yellowDBP shows blue photoluminescence, the deep redDBI is nonfluorescent. Both compounds give rise to two reversible redox transitions at E 1 / 2 =−2.03 V, −2.75 V (DBP ) and −1.52 V, −2.30 V (DBI ; THF, vs. FcH/FcH + ). The higher electron affinity ofDBI agrees with a lower calculated LUMO energy level [−0.57 eV forDBI with respect toDBP @HF//SCS‐MP2/def2‐TZVP] and a higher Lewis acidity of its boron centers, which is reflected in the trend of adduct formation with small Lewis bases (MeCN, F − ). The thermochemistry underlying this trend, as well as the mechanism of fluorescence quenching inDBI, are revealed by state‐of‐the‐art quantum chemical calculations. It is suggested that the nonradiative deactivation occurs via a low‐lying, doubly excited state. Abstract : Doubly exciting : Twofold benzannulation of diboraanthracene boosts the fluorescence but weakens the Lewis acidity. In contrast, attachment of two phenylene moieties via formal σ bonds renders the resulting borane a stronger Lewis acid, but completely quenches its photoluminescence. The nonradiative deactivation likely proceeds via an energetically low‐lying doubly excited state.